2021
DOI: 10.1177/14644207211005790
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microstructure and precipitate formation on mechanical and corrosion behavior of friction stir processed AA6061 alloy using different cooling media

Abstract: The present work studies the effect of microstructure and precipitate formation on mechanical and corrosion characteristics of friction stir processed AA6061 alloy using different cooling technologies (cryogenic and water cooling). The results revealed that recrystallized fine grains formed in all friction stir processing samples (grain size within a range of 2–6 µm) as a result of dynamic recovery and recrystallization, while samples processed in cooling-assisted friction stir processing resulted in better gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…As a result of the dissolving of second phase particles and the decrease in dislocation densities, the hardness of the FSWed samples decreases at SZ. 22 The average hardness in SZ for the weld with interlayer (85 Hv) is higher as compared to the weld without interlayer (65 Hv) due to the formation of hard IMCs which was discussed in SEM and XRD analysis ( Intermetallic behavior ). The hardness of weld with interlayer is directly influenced by the distribution of detached interlayer particles and the formation of IMCs.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…As a result of the dissolving of second phase particles and the decrease in dislocation densities, the hardness of the FSWed samples decreases at SZ. 22 The average hardness in SZ for the weld with interlayer (85 Hv) is higher as compared to the weld without interlayer (65 Hv) due to the formation of hard IMCs which was discussed in SEM and XRD analysis ( Intermetallic behavior ). The hardness of weld with interlayer is directly influenced by the distribution of detached interlayer particles and the formation of IMCs.…”
Section: Resultsmentioning
confidence: 97%
“…After 60 days, the samples were removed, and pickling was performed in a 10 vol% nitric acid solution at 60 o C. The final weight of the samples was measured and the corrosion rate was calculated using the following equation (1). 22 Later, the corroded samples were examined using the optical microscope.where CR- Corrosion rate (mpy), W- Weight loss (mg/inch 2 ), D- Density of the samples (2.7 g/cm 3 ), A- Exposed area (mm 2 ) and T- immersion time (hrs). The PDP method was performed using CHI604 E electrochemical workstation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Hence, FSW was also successfully employed to weld similar Al alloys and dissimilar materials such as Al to Mg, Al to Cu and Al to steel. [7][8][9] Although FSW produced fine and dynamically recrystallized grains, the weld thermal cycle causes thermal softening at the stir zone (SZ), reducing the corrosion resistance and weld joint strength. 10 The strength loss occurs mainly in precipitation-hardened alloys like AA6061 due to the precipitates dissolution and coarsening at elevated temperatures during FSW.…”
Section: Introductionmentioning
confidence: 99%
“…10 The strength loss occurs mainly in precipitation-hardened alloys like AA6061 due to the precipitates dissolution and coarsening at elevated temperatures during FSW. 11 The level of strength loss in the weld region during FSW of precipitation-hardened Al alloys is determined by the weld parameters, and it occurs even when optimum weld parameters are used [12][13][14] Various researchers showed that post-weld heat treatment (PWHT) could restore the strength loss of FSWed Al alloy joints. 15,16 From the literature survey, it was observed that optimization of FSW process parameters and PWHT are time consuming, and PWHT is not feasible in some practical applications.…”
Section: Introductionmentioning
confidence: 99%